PERAN SUMBER DAYA MANUSIA BUMDES DALAM MENINGKATKAN PEREKONOMIAN DESA LABUHAN JAMBU KABUPATEN SUMBAWA - S Susmita; Wahyu Haryadi; Roos Nana Sucihati (Pusat Riset dan Publikasi, 2023)
This study aims to know the role of human resource of Village Owned Enterprise (VOE) in improving village economy in Labuhan Jambu Village, Tarano Sub-District, Sumbawa District. The type of this study was associative study. The type of data used is quantitative data in the form of the results of respondents' answers obtained directly through a questionnaire. The population in this study were all BUMDes managers in Labuhan Jambu Village, Tarano Sub-District, Sumbawa District, totaling 213 people, while the number of samples was determined using the Slovin formula. The calculation results show that the number of samples is 68 people. All data that has been collected will then be processed using the SPSS program. SPSS output in the form of results will be analyzed and interpreted using simple linear regression analysis techniques, partial parameter hypothesis testing (t test), and the coefficient of determination test (R2). The results showed that BUMDes human resources had a positive and significant effect on the economy of Labuhan Jambu Village, Tarano Sub-District, Sumbawa District. The ability of BUMDes human resource variables to explain changes in economic variables in the village of Labuhan Jambu, Tarano Sub-District, Sumbawa District is 61.4%, while the remaining 38.6% is influenced by other variables outside this research model.